Periodic delay orbits and the polyfold implicit function theorem - Albers, Peter; Seifert, Irene (Arxiv, 2020)
We consider differential delay equations of the form $\partial_tx(t) = X_{t}(x(t - τ))$ in $\mathbb{R}^n$, where $(X_t)_{t\in S^1}$ is a time-dependent family of smooth vector fields on $\mathbb{R}^n$ and $τ$ is a delay parameter. If there is a (suitably non-degenerate) periodic solution $x_0$ of this equation for $τ=0$, that is without delay, there are good reasons to expect existence of a family of periodic solutions for all sufficiently small delays, smoothly parametrized by delay. However, it seems difficult to prove this using the classical implicit function theorem, since the equation above is not smooth in the delay parameter. In this paper, we show how to use the M-polyfold implicit function theorem by Hofer-Wysocki-Zehnder [HWZ09, HWZ17] to overcome this problem in a natural setup.